Test Research on Fuselage Panel Subjected to Internal Pressure Load - Zang Weifeng; Chen An; Dong Dengke (Hangkong gongcheng jinzhan, 2018)
Internal pressure is a severe cyclic load for fuselage structure, and it is important to investigate the fatigue and damage tolerance characters of fuselage panel under internal pressure. Boundary condition simulation of fuselage panel subjected to internal pressure load is challenging, and the quality of the simulation influences the range of transition area and even the stress distribution size in examining area. To investigate the stress distribution of fuselage panel subjected to internal pressure, a new test method is proposed. “D” jig is utilized to simulate the longitudinal boundary conditions of fuselage panel, and “Arch” connectors are utilized to simulate the circumferential boundary conditions. Airtight end-plate is utilized to simulate the end of the fuselage barrel. Test fixture and fuselage panel specimen are designed and manufactured according to the boundary simulation requirements. Tests are conducted based on the proposed method. The test results show that hoop stress and axial stress in transition area are much more lower than in the test area. Hoop stress, axial stress and normal displacement in the test area are consistent with theoretic results. The proposed test method settle for engineering precision requirements and provides reference for configuration-selection tests of fuselage panel subjected to internal pressure load.